Penerapan Metode Costumer Relationship Management Pada Fitur Sistem Penjualan Produk Kecantikan Berbasis Web (Studi Kasus: Toko Id.Maskmask) - Maria Sri Wulandari; Rahayu Noveandini (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Id.Maskmask is a shop that sells various beauty tools in the form of masks, body lotions, body scrubs, serums, and face mists. Currently, sales of beauty products are applied by the Id.Maskmask stores are still using the old method, namely WhatsApp as a medium for ordering and Instagram as a promotional medium to offer products and promotions to consumers and facilitate the relationship between sellers and buyers. It is necessary to make a website to complete transactions, report sales, and review or comment space to determine customer satisfaction with Id.Maskmask store products. In building this system using the Customer Relationship Management (CRM) method and this design process using the Navigation Structure and UML (Unified Modeling Language). In making applications using programming languages (HTML, PHP, CSS, JavaScript), jQuery as a library, MySQL or phpMyAdmin as a database, and Bootstrap as a framework. While the use of smartphones is not responsive in appearance, it is neat in terms of button layout, but the functions and usability are expected with the Google Chrome browser and web browser. This application will make it easier for customers to order and transact and provide reviews of stores regarding consumer satisfaction with products safely anytime and anywhere.